Lord of Chance: Rogues to Riches, #1 (Rogues to Riches, ,, 2017)
Disguised as a country miss, Charlotte Devon flees London, desperate to leave her tattered reputation behind. In Scotland, her estranged father’s noble blood will finally make her a respectable debutante. Except she finds herself accidentally wed to a devil-may-care rogue with a sinful smile. He’s the last thing she needs…and everything her traitorous heart desires. Charming rake Anthony Fairfax is on holiday to seek his fortune…and escape his creditors. When an irresistible Lady Luck wins him in a game of chance—and a slight mishap has them leg-shackled by dawn—the tables have finally turned in his favor. But when past demons catch up to them, holding on to new love will mean destroying their dreams forever.

Lord of Night: Rogues to Riches, #3 (Rogues to Riches, ,, 2017)
Unlike proper debutantes, Miss Dahlia Grenville is secretly Robin Hood in a bonnet. Her home for wayward girls has too many dependents and not enough donations. But just as she’s about to pull off the heist of the Season, she tumbles straight into the arms of the handsome detective who has sworn to deliver Mayfair’s mysterious thief straight to the gallows. Highly principled Bow Street runner Simon Spaulding’s world is black and white. There's no mastermind too clever, no criminal alive who can escape the hangman. Until he realizes the delightful young lady he’s been courting is a liar and a thief. Suddenly, his career—and his heart—are in peril. How can he bring her to justice when it means losing her forever?

Lord of Pleasure: Rogues to Riches, #2 (Rogues to Riches, ,, 2017)
Nondescript “good girl” Miss Camellia Grenville only ever opens her mouth when forced to sing at her family’s musicales. That is, until the night she infiltrates the ton’s most scandalous masquerade ball on behalf of her sister, and finds herself in the arms—and the bed—of the one man she’d sworn to hate. Irresistibly arrogant and unapologetically sensuous, infamous rake Lord Wainwright always gets his way. When he accepts a wager to turn his rakish image respectable in just forty days, he never anticipates falling for an anonymous masked lover...or that discovering her identity would destroy them both.

My One and Only Duke (Rogues to Riches, ,, 2018)
Meet the highly unconventional Wentworth family in this charming USA Todaybestseller with a Cinderella twist, perfect for fans of Mary Balogh. One minute, London banker Quinn Wentworth is facing execution. The next, he's declared the long-lost heir to a dukedom. Quinn has fought his way up from the worst slums, and now he's ready to use every dirty trick he knows to find the enemy who schemed against him. Jane Winston, widowed and pregnant, crosses paths with Quinn while her father is preaching to the prisoners. Believing his days are numbered, Quinn offers her marriage as a way to guarantee her independence and provide for her child. Neither thinks they'll actually have a future together. He's a wealthy gutter rat out for vengeance. She's a minister's daughter who must turn a marriage of desperation into a proper ducal union. Are they doomed from the start or destined for a happily-ever-after? Also includes the bonus novella Once Upon a Christmas Eve from New York Times bestselling author Elizabeth Hoyt! When his carriage wheel snaps in a snowstorm, Adam Rutledge, Viscount d'Arque, is forced to seek shelter at the home of the most maddening, infuriating, and utterly beguiling woman he's ever met. "Skillfully crafted and exquisitely written, Burrowes' latest is pure gold; a brilliant launch to a promising series." —Library Journal "Burrowes is a writer of towering talent." —USA Today Happy Ever After

When a Duchess Says I Do (Rogues to Riches, ,, 2019)
Treat yourself to a delightful Regency romance with a fairy-tale twist "much in the manner of Mary Balogh." (Kirkus) Duncan Wentworth once tried his hand at rescuing a damsel in distress long ago, and he's vowed he'll never make that mistake again. Yet when he comes across a stranger in the poacher-infested woods of his estate, decency compels him to offer the lady aid. Matilda is whip-smart, she can read Duncan's horrible penmanship, and when she wears his reading glasses all Duncan can think about is naughty Latin poetry. Widowed duchess Matilda Wakefield can't entrust her secrets to Duncan without embroiling him in the problems that sent her fleeing from London, but neither can she ignore a man who's honorable, a brilliant chess player, and maddeningly kissable. She needs to stay one step ahead of the enemies pursuing her, and falling into Duncan's arms is a distraction she can't afford-or they'll both pay the price. "Grace Burrowes is terrific!" —Julia Quinn "Grace Burrowes is a romance treasure." —Tessa Dare Library Journal Best of the YearPublishers Weekly Bestseller! BookPage "2019 Most Anticipated Romances"Bookish "Spring 2019 Must-Read Romances"